Fabrication of white light emitting diodes via high yield surface passivated carbon quantum dots doped with terbium - Pratap, Ravi; Parmar, Avanish Singh (Royal Society of Chemistry, 2023)
Exploiting the unique characteristics of various materials to create novel hybrid materials opens up innovative possibilities for cutting-edge applications across numerous fields. Here, we have synthesized novel surface functionalized photoluminescent carbon quantum dots (CQDs) doped with a rare-earth element (Tb3+) for white light emitting diodes. High quantum yield CQDs were produced utilizing Plumeria leaves as a precursor using a one-step hydrothermal approach, and further, its optical characterization was thoroughly investigated. Herein, the functionalized CQDs demonstrate excitation-independent electroluminescence performance. The UV-LED chip and functionalized CQD were combined to create a device that emits cold white light with Commission Internationale de L'Eclairage coordinates of (0.33, 0.34), a corresponding correlated color temperature of 4995 K and color rendering index of 84.2.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Carbon; Hybrid materials; Nanocrystals; Rare earths; Terbium; Carbon quantum dots; Cutting edges; Functionalized; Hybrids material; Novel surfaces; Optical characterization; Performance; Synthesised; UV LEDs; White light emitting diodes; Semiconductor quantum dots